2016
DOI: 10.1177/0021998316674265
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of high-performance wood polymer nanocomposites using multi-walled carbon nanotubes

Abstract: Effect of industrial grade multi-walled carbon nanotubes on mechanical, decay, and thermal properties of wood polymer nanocomposites was investigated. To meet this objective, pine wood flour, polypropylene with and without coupling agent (maleic anhydride grafted polypropylene), and multi-walled carbon nanotube (0, 1, 3, 5 wt%) were compounded in a twin screw co-rotating extruder. The mass ratio of the wood flour to polypropylene was 50/50 (w/w) in all compounds. Test specimens were produced using injection mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…In other words, the availability of moisture is a prerequisite for biological decay in a material. 19 The results showed that by the incorporation of CNT into the compound, the susceptibility of the composite specimens to microbial degradation reduced. This is because of more durable for moisture content by nanoparticles, which caused the composites less accessible for the fungal activities, and consequently reduced the susceptibility of WPC to microbial degradation.…”
Section: Weight Lossmentioning
confidence: 98%
See 3 more Smart Citations
“…In other words, the availability of moisture is a prerequisite for biological decay in a material. 19 The results showed that by the incorporation of CNT into the compound, the susceptibility of the composite specimens to microbial degradation reduced. This is because of more durable for moisture content by nanoparticles, which caused the composites less accessible for the fungal activities, and consequently reduced the susceptibility of WPC to microbial degradation.…”
Section: Weight Lossmentioning
confidence: 98%
“…This result is consistent with previous studies. 19,[35][36][37][38] The SEM micrographs clearly displayed the position of nanoparticles in the composites with different treatments (Figure 2). As can be seen, the number of cavities on the surface of the specimens decreased the increasing amount of CNT.…”
Section: Weight Lossmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, there was shown the importance of polymers in various military protection applications [1][2][3][4], and was demonstrated that the reinforcement of such polymers conducts to better composite materials, which possess higher strength and higher modulus [2,[5][6][7][8][9][10], in order to, e.g., reduce blunt trauma [10].…”
Section: Introductionmentioning
confidence: 99%